Análisis comparativo de producciones per cápita y densidades de residuos residenciales de 5 ciudades del Ecuador. - Chalacán Guevara, Alex David (2023)
In this research project, a comparative analysis was conducted on per capita waste generation (PCWG) and residential solid waste (RSW) densities in five cities in Ecuador: Riobamba, Otavalo, Tena, Baños de Agua Santa, and Chambo. The main objective of this study was to compare the means of PCWG and RSW densities in the five cities and their four socioeconomic strata. Data on PCWG and densities were collected and consolidated for these cities. Subsequently, an analysis of variance (ANOVA) was performed in two scenarios: A) comparison of the four strata within each city, and B) comparison of the five cities within each stratum. The Tukey test was also applied in both scenarios to identify specific significant differences and groupings among cities and strata. The results of the comparative analysis showed significant differences in the means of PCWG and densities between socioeconomic strata within the same city, mainly occurring between high and low strata. On the other hand, in the comparison between cities, it was determined that stratum A is the only stratum with similar PCWG in all five towns. Similar densities were found in strata C and D. However, these similarities do not represent the behavior of the populations, as they may vary due to the demographic, economic, and consumption habits of each stratum. Even if the means of PCWG are similar, there may still be differences in the types and proportions of different waste components. Therefore, it is necessary to develop more effective policies and strategies in solid waste management tailored to each city's specific characteristics, aiming to reduce waste generation, promote recovery and recycling, and foster sustainable waste management